Anti-hypertensive Herbs and their Mechanisms of Action: Part I - Al Disi, Sara S.; Anwar, M. Akhtar; Eid, Ali H. (Frontiers in Pharmacology, 2016)
The use of herbal therapies for treatment and management of cardiovascular diseases is increasing. Plants contain a bounty of phytochemicals that have proven to be protective by reducing the risk of various ailments and diseases. Indeed, accumulating literature provides the scientific evidence and hence reason d’etre for the application of herbal therapy in relation to cardiovascular diseases. Slowly, but absolutely, herbal remedies are being entrenched into evidence-based medical practice. This is partly due to the supporting clinical trials and epidemiological studies. The rationale for this expanding interest and use of plant based treatments being that a significant proportion of hypertensive patients do not respond to Modern therapeutic medication. Other elements to this equation are the cost of medication, side-effects, accessibility and availability of drugs. Therefore, we believe it is pertinent to review the literature on the beneficial effects of herbs and their isolated compounds as medication for treatment of hypertension, a prevalent risk factor for cardiovascular diseases. Our search utilized the PubMed and ScienceDirect databases, and the criterion for inclusion was based on the following keywords and phrases: hypertension, high blood pressure, herbal medicine, complementary and alternative medicine, nitric oxide, vascular smooth muscle cell proliferation, hydrogen sulfide, nuclear factor kappa-B, oxidative stress and epigenetics/epigenomics. Each of the aforementioned keywords was co-joined with plant or herb in question, and where possible with its constituent molecule(s). In this first of a two-part review, we provide a brief introduction of hypertension, followed by a discussion of the molecular and cellular mechanisms. We then present and discuss the plants that are most commonly used in the treatment and management of hypertension.